Analysis of Anxiety, Stress, Self-Confidence, and Motivation of KU III Swimming Athletes in Achieving Goal Setting - Afifah, Ihsantin Nazih; Setyawati, Heny; Raharjo, Agus (Universitas Negeri Semarang, 2025)
Introduction: Goal setting is a critical psychological skill in athletic performance, enabling athletes to establish clear, challenging, and measurable targets. In addition to increasing motivation and self-confidence, goal setting also helps athletes manage stress and anxiety, making goal setting an important strategy in training athletes to achieve peak performance. Objectives: This study aims to analyze the relationship between psychological factors stress, anxiety, self-confidence, and motivation and goal-setting among KU III (Age Group III, 12-13 years old) swimmers in Semarang. Method: Using a mixed-methods sequential explanatory design, the research involved 26 athletes selected via purposive sampling. Quantitative data were collected using standardized scales (DASS-21, TSCI, SOQ, and a goal-setting scale) and analyzed with correlation techniques, while qualitative data from in-depth interviews were analyzed thematically. Result: The results revealed that self-confidence (r = 0.652, p = 0.000) and motivation (r = 0.742, p = 0.000) had a strong, significant positive relationship with goal-setting. In contrast, anxiety (r = -0.328) and stress (r = -0.119) showed weak, non-significant negative relationships. Simultaneously, the four psychological factors accounted for 75.1% (R² = 0.751) of the variance in goal-setting effectiveness. Qualitative findings identified key themes, including triggers of anxiety/stress, coping strategies, sources of self-confidence, and the dominance of intrinsic motivation. Conclusion: The study concludes that high self-confidence and strong intrinsic motivation are the primary drivers of effective goal-setting in young swimmers, while unmanaged anxiety and stress can be detrimental.